First record of the freshwater copepod Eucyclops titicacae Kiefer, 1957, new rank (Copepoda, Cyclopoida) in Colombia - Fuentes-Reinés, Juan Manuel; Suárez-Morales, Eduardo (Biota Neotropica, 2013)
The freshwater cyclopoid copepod Eucyclops titicacaeKiefer, 1957, new rank, was previously known as a subspecies of E. neumani (Pesta, 1927). Hitherto, it was recorded only from Lake Titicaca in Peru and Lake Valencia in Venezuela. This species is here recorded from Laguna Navío Quebrado, La Guajira, northern Colombia. This is the first record of E. titicacae in Colombia and the third locality in which this species has been reported from. We provide comparative data on the morphology of this copepod. The Colombian specimens have the combination of diagnostic features of E. neumani titicacae as reported in both the original description and subsequent taxonomical accounts, including: 1) spinules on caudal rami not reaching halfway the outer margin; 2) caudal rami length/width ratio= 6.0; 3) length/width ratio of third endopodal segment of fourth leg=1.66; 4) inner spine of fifth leg being shorter than the two adjacent setae. The consistent morphologic differences and the isolation of E. neumani titicacae with respect to E. neumani neumani, each related to a different biogeographic subregion in South America, support the notion that these are two separate species, E. neumani and E. titicacae. Considering this interesting addition, the number of species of Eucyclops known from Colombia increases to 8; a key for the identification of these species is also provided.